Improvement of home composting process of food waste using different minerals. (March 2018) - Margaritis, M.; Psarras, K.; Panaretou, V.; Thanos, A.G.; Malamis, D.; Sotiropoulos, A.
Highlights: Home composting of kitchen waste could be improved by using mineral additives such as zeolite and perlite. The use of additives completes the composting process in 18 days max. Household composting process needs to be further improved in the future. The use of zeolite regulates the concentrations of ammonia and consequently the nitrate in the substrate. Abstract: This article presents the experimental study of the process of composting in a prototype home-scale system with a special focus on process improvement by using different additives (i.e. woodchips, perlite, vermiculite and zeolite). The interventions with different bulking agents were realized through composting cycles using substrates with 10% additives in specific mixtures of kitchen waste materials. The pre-selected proportion of the mixtures examined was 3:1:1 in cellulosic:proteins:carbohydrates, in order to achieve an initial C/N ratio equal to 30. The control of the initial properties of the examined substrates aimed at the consequent improvement of the properties of the final product (compost). The results indicated that composting process was enhanced with the use of additives and especially the case of zeolite and perlite provided the best results, in terms of efficient temperature evolution (>55 °C for 4 consecutive days). Carbon to nitrogen ratios decreased by 40% from the initial values for the reactors were minerals were added, while for the bioreactor tested with woodchips the reduction was slight, showing slowest degradation rate. Moisture content of produced compost varied within the range of 55–64% d.m., while nutrient content (K, Na, Ca, Mg) was in accordance with the limit values reported in literature. Finally, the composts obtained, exhibited a satisfactory degree of maturity, fulfilling the criterion related to the absence of phytotoxic compounds.